Annual Plan 1971-72 Mysore - Planning Commission (Planning Commission, 1971)
The year 1970 marks the beginning of what has come to be known as the second development decade. The budget speech for 1970-71 of Sri. Ramakrishna Hegde, Finance Minister of the state outlines the Following major goals for achievement during this decade A total investment, by Government and the private sector, of about R‘s. 2,000 crores leading to substantial progress towards doubling the annual rate of growth per capita iconize Employment for every able-bodied adult citizen who needs it self-sufficiency in food grains and export to places outside the State. Eradication of the economic and social handicaps that sustain untouched ability. Diversification and widespread growth of industries and encouragement to the entrepreneur Improvement in the quality the social service, particularly in Education and’ Medical Services.
Mysore State
Government of Mysore
Keywords: Problems and Strategy; Minor Irrigation with special attention to the sinking of irrigation wells; Soil Conservation; Ayacut development; Intensive area Programmes; High yielding varieties Programme; Improved soil and water management; scientific application of manures and fertilizers; Increased coverage o plant protection measures; Economic situation in Mysore State; Financial Outlook; Programme For Backward Areas Communities.